2021
DOI: 10.3390/foods10050990
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptability and Sensory Profile of Sustainable Paper-Based Packaging

Abstract: Sustainability appears to be increasingly important to consumers. In order for companies to reach their sustainability targets and offer more environmentally friendly solutions to consumers, food producers and retailers have begun to change their packaging to more recyclable, bio-based and biodegradable packaging. This study evaluated the sensory characteristics of paper-based prototype packages developed for two product categories (biscuit and meat packages) using a trained sensory panel. Consumer liking, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Overall, the paper-based packages did not meet participants' expectations, but they all agreed that the design was headed in the right direction. To validate the results of this study, a quantitative study with 130 participants was conducted with results corresponding with this study [49]. In summary, the key message that emerged from the discussions was the "3Rs"-Reduce, Reuse, and Recycle -which should be the main points to consider when designing a sustainable packaging.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Overall, the paper-based packages did not meet participants' expectations, but they all agreed that the design was headed in the right direction. To validate the results of this study, a quantitative study with 130 participants was conducted with results corresponding with this study [49]. In summary, the key message that emerged from the discussions was the "3Rs"-Reduce, Reuse, and Recycle -which should be the main points to consider when designing a sustainable packaging.…”
Section: Discussionmentioning
confidence: 77%
“…A growing trend in the food industry is a shift away from just showing product images on the package to using transparent packaging materials, which allow consumers to see exactly what they are buying [47]. Previous studies showed that transparent packaging increases expected freshness, expected quality, and purchase intent in various food categories [48,49]. This suggests that transparent packaging has an effect on consumer behavior [47].…”
Section: Discussionmentioning
confidence: 99%
“…Paper is a bio-based, recyclable, and biodegradable material generally available as a thin sheet made of cellulosic fibers [ 4 ]. It is a highly suitable material for addressing sustainable and eco-friendly packaging issues [ 5 ]. Researchers from the Institute of Energy and Environment, Germany, revealed that paper-based packaging has a lower impact on the environment than other traditional materials.…”
Section: Introductionmentioning
confidence: 99%
“…based on paper-and-pencil or online questionnaires [2,3,10,[12][13][14]17], and two (~10%) used qualitative focus group interview approaches [11,19]. Furthermore, of the nine studies that included sensory analysis, two studies exclusively applied analytical sensory evaluation techniques using trained or semi-trained sensory panels [6,18], six studies employed hedonic tests to assess acceptability using non-trained panels (consumers) [5,[7][8][9]15,16], while only one study used both [20]. Methods used in the studies demonstrate that the usual techniques of sensory and consumer research are also applicable to research on sustainable foods.…”
mentioning
confidence: 99%
“…Lignou and Oloyede [20] used both analytical (trained panel) and hedonic (consumers) sensory analysis in their study on food packages. They employed several methods to study the sensory profile and consumer acceptability of sustainable paper-based packaging for two product categories (biscuit and meat).…”
mentioning
confidence: 99%